2013
DOI: 10.1097/ccm.0b013e3182758734
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Versus Histamine 2 Receptor Antagonists for Stress Ulcer Prophylaxis in Critically Ill Patients

Abstract: In critically ill patients, proton pump inhibitors seem to be more effective than histamine 2 receptor antagonists in preventing clinically important and overt upper gastrointestinal bleeding. The robustness of this conclusion is limited by the trial methodology, differences between lower and higher quality trials, sparse data, and possible publication bias. We observed no differences between drugs in the risk of pneumonia, death, or ICU length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(116 citation statements)
references
References 26 publications
7
95
0
14
Order By: Relevance
“…Randomized trials and meta-analyses support the evidence that PPIs reduce the rate of bleeding (Buendgens et al, 2016). PPIs are more effective than H2 receptor antagonists, although they failed to show any effect on overall mortality and on time of ICU stay (Krag et al, 2015;Alhazzani et al, 2013).…”
Section: Stress Gastric Ulcers In Cancer Patientsmentioning
confidence: 65%
“…Randomized trials and meta-analyses support the evidence that PPIs reduce the rate of bleeding (Buendgens et al, 2016). PPIs are more effective than H2 receptor antagonists, although they failed to show any effect on overall mortality and on time of ICU stay (Krag et al, 2015;Alhazzani et al, 2013).…”
Section: Stress Gastric Ulcers In Cancer Patientsmentioning
confidence: 65%
“…Regarding disagreement, the primary literature deserves mention. While the majority of clinical trials demonstrate the noninferiority of H2RAs at preventing clinically significant gastric bleeding, some suggest that PPIs are a preferred treatment option (5,11).…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity can range from endoscopic evidence of mucosal damage to clinically significant bleeding. Larger studies assessing the presence of mucosal damage report prevalence rates of any extent of damage in roughly 75% -100% of critically ill patients, while clinically significant bleeding occurs on average in < 0.5% -6% of patients (2)(3)(4)(5). Risk factors associated with the development of stressrelated mucosal disease have been recognized, including continuous mechanical ventilation for greater than 48 hours and coagulopathy (1).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, SUP is a common practice, as supported by several randomized trials and the guidelines of the Surviving Sepsis Campaign, although SUP does not appear to influence the risk of death in ICU patients. 13,14,18 Regarding interest in re-evaluating SUP in a RCT comparing placebo with PPI, 85% of physicians agreed that a trial is necessary due to their concerns about lack of benefit and possible harmful effects of acid suppression. In Australia, the pilot randomized POPUP (Pantoprazole Or Placebo for Stress Ulcer Prophylaxis) trial of 214 patients was recently completed on this topic (trial registration no., ACTRN126130 00807752).…”
Section: Discussionmentioning
confidence: 99%
“…The study at issue showed that PPIs were associated with a 60% relative risk reduction in clinically important stress ulcer-related GI bleeding when compared with H2RAs. 13 In this survey, the agents of choice for SUP were ranitidine in the H2RA class and pantoprazole in the PPI class. Regardless of the agent used, the respondents cited enteral as the preferred method of administration, which is similar to survey findings among Australian prescribers.…”
Section: Discussionmentioning
confidence: 99%